1995
DOI: 10.4315/0362-028x-58.11.1249
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Growth and Aflatoxin Production of Aspergillus flavus by Lactobacillus Species

Abstract: A mixture of Lactobacillus species from a commercial silage inoculum reduced mold growth and inhibited aflatoxin production by Aspergillus flavus subsp. parasiticus. Actively growing Lactobacillus spp. cells totally inhibited germination of mold spores. Culture supernatant broth from the mixture of strains inhibited mold growth but did not destroy mold spore viability. Some mold spores were observed microscopically to have germinated and produced short nonbranching germ tubes; then growth ceased. While the pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 0 publications
3
62
1
3
Order By: Relevance
“…Some LAB can inhibit mould growth and /or reduce mycotoxin production. Several investigations have demonstrated that LAB from dairy, meat, silage and gut environments either suppressed mycotoxin biosynthesis or effectively removed preformed mycotoxins 31,49,63,64,78,120 .…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…Some LAB can inhibit mould growth and /or reduce mycotoxin production. Several investigations have demonstrated that LAB from dairy, meat, silage and gut environments either suppressed mycotoxin biosynthesis or effectively removed preformed mycotoxins 31,49,63,64,78,120 .…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…The effect of small molecular weight metabolites produced by Lactobacillus species in the inhibition of aflatoxin production was demonstrated by Gourama & Bullerman (21). In their experiments a mixture of Lactobacillus species from a silage inoculant was cultivated inside of a dialysis sack, while A. parasiticus was cultivated on the outside.…”
Section: Inhibition Of Mycotoxin Productionmentioning
confidence: 94%
“…Foodborne and food grade LAB have been studied much more than Bacillus species or propionic bacteria and their antifungal activities have been reported by several authors throughout the years (20,21,22,23,24,25,26,27). Table 1 shows some of the publications that have demonstrated the antifungal activity of LAB, which vary from broad to very specific among and within species.…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%
“…However, to date, there are few practical methods for preventing aflatoxin contamination, and it is therefore critical to develop effective methods for prevention. A limited number of reports have shown that a good selection of Lactic Acid Bacteria (LAB) could allow the control of mould growth and improve the shelf life of many fermented products and, therefore, reduce health risks due to exposure to mycotoxins (Gourama &Bullerman, 1995b andDal Bello et al, 2007). El-Nezami et al (1998a) and Gratz et al (2006) demonstrated that the probiotic Lactobacillus rhamnosus (L. rhamnosus) strain GG is able to bind the potent hepatocarcinogenic aflatoxin B 1 (AFB 1 ).…”
mentioning
confidence: 99%